Isolation, Affinity Purification, and Identification of Piglet Small Intestine Mucosa Receptor for Enterotoxigenic Escherichia coli K88ac+ Fimbriae - Fang, Lin (American Society for Microbiology, 2000)
An affinity chromatography technique was utilized to isolate and purify the receptors of Escherichia coli K88ac(+) fimbriae from the mucus of the small intestines of newborn piglets. Purified K88ac+ fimbriae were covalently immobilized onto a beaded agarose matrix (Sepharose 4B). The immobilized fimbriae were used for the affinity purification of the K88ac+ receptors. Only two major proteins were tightly and specifically bound to the immobilized fimbriae after the column containing bound receptor was washed exhaustively with a buffer containing a high concentration of salt and a detergent. The receptors were eluted as a single component at a low pH. The isolated proteins were then subjected to enzyme-linked immunosorbent assay, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and Western blot (immunoblot) analyses. The two proteins were of high purity, were responsible for nearly all of the fimbrial binding capacity of the crude mucus, and had molecular masses of 26 and 41 kDa. The method for isolation of E. coli binding proteins is simple and yields purified intestinal receptors in a single chromatographic run. The intestinal mucus of different piglets has different proportions of the two receptor proteins.